Leveraging the Potential Benefits of Medicinal Plants in the Management of Substance Abuse - Asdaq, Syed Mohammed Basheeruddin (Asian Journal of Pharmaceutics (AJP), 2024)
There is a global increase in the number of reported cases of drug misuse and addictions. In addition to several health issues, the addict-forming substance affects society economically. Cocaine, heroin, opium, alcohol, nicotine, and marijuana are a few of the major substances that are abused. These agents’ inexpensive cost and wide availability contribute to their abuse. Many conventional medications are available to treat substance abuse-related disorders, but they come with several side effects. One potential treatment option for the issues experienced by addicts is the use of alternative medications obtained from natural sources. The current study provided an overview of a few published studies that suggested herbal medication may be effective in reducing withdrawal symptoms. The information was obtained from the Web of Science, NCBI, PUBMED, EMBASE, and Google Scholar. The retrieved data were analyzed to determine the active constituent present in the plant material, the type of addict substance tested, and the possible mechanism identified. The research identified some of the plants that have been reported to be effective in the management of substance abuse complications. Information analysis revealed that plant-based medications helped lessen anxiety, pain, insomnia, and deviant conduct, among other consequences of substance usage. Withdrawal as well as dependence liabilities due to addictive agents were found to be reduced. The plant-based medicines exhibited their action on brain centers involving dopaminergic, serotonergic, and adrenergic transmission. The observations from the study revealed that herbal medicines were effective in the management of substance abuse complications. However, most of the investigations were conducted using preclinical testing models. Therefore, it can be said that while herbal medications showed promise in treating drug abuse-related problems, further study is necessary to pinpoint the exact safety and effectiveness of these agents.